1988
DOI: 10.1111/j.1532-5415.1988.tb03429.x
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized Cognitive Impairment in Cardiac Rehabilitation Patients

Abstract: To determine the prevalence of unrecognized brain dysfunction accompanying chronic severe cardiac disease, we examined 20 clinically stable consecutive admissions to a cardiac rehabilitation service who were free of known stroke or dementia. Age range was 47 to 85 years (mean +/- SEM, 72.5 +/- 2.1 years), the male: female ratio was 10:10. Multiple cognitive deficits including significant memory impairment and disorientation were present in eight patients (40%), and seven of these eight patients were unable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 13 publications
2
41
2
Order By: Relevance
“…First, CVS may reflect a more generalized vascular disturbance, with resulting effects on the central nervous system. Second, the CVS observed may be indicative of heart failure resulting in hypoperfusion in the brain (Barclay et al, 1988;Meyer et al, 1995). In contrast, CVS was unrelated to digit span and verbal fluency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, CVS may reflect a more generalized vascular disturbance, with resulting effects on the central nervous system. Second, the CVS observed may be indicative of heart failure resulting in hypoperfusion in the brain (Barclay et al, 1988;Meyer et al, 1995). In contrast, CVS was unrelated to digit span and verbal fluency.…”
Section: Discussionmentioning
confidence: 99%
“…Three specific CVS were targeted (i.e., cardiac murmur, dyspnea, edema in lower limbs), all of which may be indicative of congestive heart failure (Barclay et al, 1988;O'Keeffe & Lye, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with VaD may also be found in stroke clinics and rehabilitation services, in particular among patients recovering from stroke, undergoing cardiac rehabilitation after myocardial infarction [53, 54], or in convalescence units after major surgery, in particular coronary artery bypass graft [55, 56] and hip fracture repair [57]. Patients with severe behavioral manifestations (apathy, agitation, uninhibited behavior) are usually seen by geriatric psychiatrists who have coined the term ‘depression-executive dysfunction syndrome of late life’ for this clinical syndrome [58, 59].…”
Section: Other Risk Factors For Vadmentioning
confidence: 99%
“…Cross-sectional clinical studies have shown cognitive impairment to be associated with cardiac arrest [6], arteriosclerosis [7], hypertension [8], CHD [8,9] and myocardial infarction (MI) [10] among the elderly. A recent longitudinal study among 73 male managers also showed CVDs to be predictors of cognitive impairment among the elderly [11].…”
Section: Introductionmentioning
confidence: 99%